Analisis Struktur Biaya dan Pendapatan Usaha Rumah Tangga Di Kecamatan Watubangga Kabupaten Kolaka “Studi pada Industri Pembuatan Tahu” - Sabarudin; Sindi Adistri (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
Analysis of the Cost Structure and Income of Household Businesses in Watubangga District, Kolaka Regency (Study on the Tofu Making Industry). This study aims to: analyze the cost structure and income of the tofu making industry so that the